2013
DOI: 10.1242/jeb.083469
|View full text |Cite
|
Sign up to set email alerts
|

Paired pulse ratio analysis of insulin-induced synaptic plasticity in the snail brain

Abstract: SUMMARYInsulinʼs action in the brain can directly alter cognitive functioning. We have recently shown that molluscan insulin-related peptides are upregulated following a conditioned taste aversion (CTA) training procedure. In addition, when mammalian insulin is superfused over the isolated Lymnaea stagnalis central nervous system, it elicits long-term synaptic enhancement at the monosynaptic connection between the cerebral giant cell and the buccal 1 (B1) motor neuron. This synaptic enhancement is thought to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Our previous studies have indicated that both mammalian insulin and MIPs significantly alter synaptic transmission in the isolated CNS at concentration in the sub-micromolar range (Murakami et al, 2013a(Murakami et al, , 2013b. Here we used a concentration of 100 nM bovine insulin for the in vivo injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have indicated that both mammalian insulin and MIPs significantly alter synaptic transmission in the isolated CNS at concentration in the sub-micromolar range (Murakami et al, 2013a(Murakami et al, , 2013b. Here we used a concentration of 100 nM bovine insulin for the in vivo injection.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments demonstrated that both bovine insulin and the human insulin receptor antibody can bind molluscan like insulin peptide (MIP) receptors (Murakami et al, 2013a(Murakami et al, , 2013b. This is because the binding site of Lymnaea MIP receptors is well conserved across phyla.…”
Section: Injection Of Bovine Insulin and Human Insulin Receptor Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when we examined the serotonergic synaptic connection between the CGC and the B1 motor neuron, we found that molluscan insulin-related peptides act to strengthen this connection (Murakami et al 2013a). Our present working hypothesis is that molluscan insulin-related peptides accomplish this by acting on the B1 motor neuron (postsynaptic neuron) but not on the CGC (presynaptic neuron) (Murakami et al 2013b). …”
Section: Function Of Insulin In Postsynaptic Neuronsmentioning
confidence: 99%
“…That is, the CGC and the B1 motor neurons both possess molluscan insulinrelated peptide receptors. To determine if the change in synaptic plasticity of the CGC-B1 synapses brought about by insulin was the result of presynaptic and/or postsynaptic alternations, Murakami et al (2013b) used the paired pulse procedure, in which the amplitude of an initial EPSP was compared with that of a second EPSP elicited shortly after the first EPSP. If the second EPSP is larger than that of the first EPSP, it is called paired pulse facilitation, whereas if the second EPSP is smaller, it is called paired pulse depression.…”
Section: Function Of Insulin In Postsynaptic Neuronsmentioning
confidence: 99%